Autorská a tematická struktura časopisu Sociální problémy: Příspěvek k sociologickému rozboru české sociologie - Janák, Dušan; Bereś, Anna (Lidé města, 2011)
The following text presents the results of the content analysis of the journal Sociální problémy (Social Problems). The given journal was been founded in 1931, and with several interruptions, was published until 1947. The analysis of the journal also represents a study of the Czech inter-war sociological discourse, at the time of its greatest development in the 1930s. The article gives an aggregative picture of the journal from the perspective of the content and structure of the individual years of its publishing. As to the structure of its authors, the article presents those who were the most productive, as well as the themes that most significantly resonated in their articles. Thematically, the journal represents a combination of quantitative and qualitative positions. In order to describe thematic structure, authors utilised the term “thematic centre”, representing a semantic field that includes various thematically-related contributions. These centres can be hierarchically sequenced according to the number of assigned texts. The dominant centres of Sociální problémy proved to be articles related to sociology (mostly foreign) itself, economy, science, nation, crisis, politics, work and family. In the article, the most important characteristics of Sociální problémy are compared with a “rival” journal Sociologická revue (Sociological Review). Despite the mutual publication barriers (authors of one journal did not contribute to the other journal) and purpose, both journals demonstrate a similar thematic structure. The discovered common thematic centres seem to be significant for all of Czech discourse at that time. Similarly, in both journals, members of the editorial teams dominated also as authors. Sociální problémy, however, amounted to approximately half of the extent of Sociologická revue and to fewer foreign contributing authors (partially on purpose). On the other hand, more experts from disciplines relative to sociology published in Sociální problémy.